The association between seasonality and the incidence of permanent pacemaker implantations due to atrioventricular block. - Doga, Reut; Yarza, Shaked; Glatman-Freedman, Aharona; Novack, Victor; Haim, Moti; Konstantino, Yuval (International Journal of Environmental Health Research, 2026)
The Winter season is associated with increased cardiovascular morbidity. Scarce data exists regarding seasonal variation and permanent pacemaker implantation (PPM) due to advanced atrioventricular (AV) block. A retrospective analysis including 759 consecutive patients with AV-block requiring PPM implantation in a tertiary university medical center was performed. The association between daily incidence of PPM implantation, season of admission, meteorological parameters and Influenza rates was assessed. Mean age was 76 and 55% were males. After adjustment for temperature, humidity, rainfall and patient comorbidities, there was a significant association between a 5-degree Celsius decrease in ambient temperatures and daily incidence of PPM implantation (adjusted RR:1.06, 95% CI 1.02–1.13; p = 0.03). In adjusted analysis stratified by seasons, gender and patient comorbidities, PPM implantation was higher among men, during the winter season as compared to the fall season (adjusted RR:1.31, 95% CI 0.99–1.75; p = 0.07). Yet, there was no significant association between PPM and influenza season (adjusted RR:1.24, 95% CI 0.86–1.78, p = 0.24). Further research is required to validate these findings and assess whether temperature decline is clearly related to AV-block or other confounding variables exist.